1992
DOI: 10.1159/000154092
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-Phosphate Dehydrogenase Variants in Hawaii

Abstract: Sequence analysis has been performed on the DNA of 13 glucose-6-phosphate dehydrogenase (G6PD) deficient males from Hawaii, 6 of Filipino, 6 of Laotian, and 1 of Chinese extraction. Four different mutations were found: A→T at cDNA nt 835, G→A at nt 871, C→T at nt 1360, and G→A at nt 1388. The mutations at nt 835 and nt 1360 have not been described previously, and the latter, in particular, appears to be relatively common. The nt 1360 mutation changes the same codon as is altered in a previously described mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…We consider that the G6PD Mahidol mutation in the Indians in Myanmar may have occurred independently in India, because intermarriage between Indians and other ethnic groups in Myanmar is rare. The G6PD Mahidol mutation has also been documented in Laotian immigrants in Hawaii (Beutler et al 1992;Hsia et al 1993), Javanese in central Java (Soemantri et al 1995), a Thai immigrant in Japan (A. Hirono, unpublished), and Chinese in Taiwan (Chang et al 1992;Tang et al 1992;Lo et al 1994;Huang et al 1996), suggesting the ancient origin of this mutation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We consider that the G6PD Mahidol mutation in the Indians in Myanmar may have occurred independently in India, because intermarriage between Indians and other ethnic groups in Myanmar is rare. The G6PD Mahidol mutation has also been documented in Laotian immigrants in Hawaii (Beutler et al 1992;Hsia et al 1993), Javanese in central Java (Soemantri et al 1995), a Thai immigrant in Japan (A. Hirono, unpublished), and Chinese in Taiwan (Chang et al 1992;Tang et al 1992;Lo et al 1994;Huang et al 1996), suggesting the ancient origin of this mutation.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have established the molecular abnormalities responsible for G6PD deficiency in several ethnic groups in Southeast Asia, including Chinese (Chang et al 1992;Tang et al 1992;Chiu et al 1993;Lo et al 1994;Saha et al 1994;Xu et al 1995;Huang et al 1996;Chen et al 1998), aboriginal tribes (the Ami, the Yami, and the Saisiat) in Taiwan (Tang et al 1995), Javanese (Soemantri et al 1995), tribes in Papua New Guinea (Wagner et al 1996;Hirono et al 1998b), islanders in Vanuatu (Ganczakowski et al 1995), people in the Solomon Islands (Hirono et al 1995), and immigrants from the Philippines and Laos (Beutler et al 1992;Hsia et al 1993). However, there has been no population-based study on molecular variants in the Indochina Peninsula and the Indonesian islands, except for Java.…”
Section: Introductionmentioning
confidence: 99%
“…It may result in neonatal jaundice, drug-induced haemolytic anaemia, favism, and chronic nonspherocytic haemo lytic anaemia [1], The mutation type and occurrence rate of each G6PD mutation in the general population of Taiwan (including Chi nese and native Taiwan aborigines) have been reported recently [2][3][4], The frequency of G6PD deficiency in the Chinese population of Taiwan is 2-3% [5,6], and in three Taiwan aboriginal tribes (Saisiat, Ami, and Yami), is 9.0, 6.1, and 0%, respectively [4], We and others have recently shown that at least 12 different types of missense mutations, including 95 A->G [2,7], 392 G->T [8], 487 G -»A [6], 493 A->G [6], 592 C^T [4,9], 835 A->T [10], 871 G h>A [4], 1004 C^A [11], 1024 C->T [8], 1360 C->T [12], 1376 G ->T [13], and 1388 G h >A [13], are respon sible for G6PD deficiency in Chinese. Of these, the 1376 mutation is the most common allele, accounting for nearly 55% of deficiency cases in the Chinese population of Taiwan [2,3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Each of these two mutations represents sever al similar or different biochemical variants. In addition, seven other mutations at nucleo tides 95, 392, 487, 493, 835, 1024 and 1360 have also been described in the Chinese and South-East Asians [12,[14][15][16][17][18][19][20]. Two common Mongoloid mutations (nt 1376 and nt 1388) represent 71 and 45% of G6PD deficiency in the Chinese of Taiwan and Singapore, respec tively [1 1,12], In addition, the Mediterranean mutation represented 10% of G6PD deficien cy in Singapore Chinese [11], Indonesian pop ulations represent about a third of the total population of South-East Asia.…”
Section: Introductionmentioning
confidence: 99%